Budaya Toleransi Studi Living Islam di Desa Balun, Lamongan - Ulum, Khoirul (UIN Sunan Kalijaga Yogyakarta, 2019)
The Cultural research in this study was captured as a form of tolerance that hold a system of meanings or sense that were formed historically. The result of this research, that the religious diversity in the Balun village community was manifested in the form of tolerance which the emphasized of willingness to accept differences, and equal treatment of fundamental fair. Tolerance of inter-religious harmony of Balun village community, expressed in the form of culture maintained in activities that bring together three religions through the religions activities such as kenduri (kenduren) and the major days of each religion, as well as the forms of places of worship standing side by side hold tolerance values as a form of harmony between religious believers implied in the term Desa Pancasila.